Shareholder or Investment Account Holder Interest: Which One Does Management of Islamic Banks Pay Attention to? - Sepky Mardian (Journal of Islamic Economics and Finance Studies, 2023)
Governance and performance studies are often viewed from the perspective of shareholders, including in Islamic banks. However, the Investment Account Holders (IAH) are equally important stakeholders. Profit-sharing contracts, the absence of representation in the Annual General Meeting, and larger fund amount place the IAH at greater risk. In reality, the impact of governance should also prioritize protecting their interests. This study examines the effect of implementing corporate governance on the performance of Islamic banks from the perspective of shareholders and IAHs. This study tabulates data from the annual reports of 14 Indonesian Islamic banks. This research has found that Islamic bank governance has no effect on performance from the perspective of IAHs. On the other hand, governance can significantly influence performance from a shareholder perspective. From the perspective of stakeholder theory, these findings explain that Islamic banks have not made IAHs the main party to pay attention to. Business policies and strategies that are overseen by corporate governance have not had an impact on wider stakeholders. The IAHs in Islamic banks should also be categorized as key stakeholders.